BARBARIANS AND NOMADS. FANTASIES AND PHOBIAS - Pálfalvi, Lajos (Porównania, 2018)
The essays of Jerzy Stempowski and Stanislaw Vincenz describe the reminiscences of the age-old agricultural cultures which have always been threatened by the nomadic people. In the Slavic mythology terms such as ”the executioners of the Slavs” have been identified with figures like Árpád. The ancient tradition and the barbaric civilization are part of the European tradition. The latter has been ennobled by Karol Modzelewski in his synthesis: Barbarian Europe, but the nomads still remain an alien element. The Hungarian historiography of the first half of the 20th century produced a deep reflection on nomadism. The eminent historian, Tibor Joó (1901-1945), reconstructed and reinterpreted the forgotten Hungarian traditions in his monograph: Hungarian Nationalism (1941).